SISTEM INFORMASI GEOGRAFIS TENTANG JUMLAH TENAGA KESEHATAN MENURUT KECAMATAN DI KABUPATEN BREBES - Yudha Ananda Ramadhan; Bambang Agus Herlambang, Ahmad Khoerul Anam (Jurnal Kesehatan, 2024)
This research is entitled Utilization of Geographic Information Systems, number of workers according to sub-districts in the Brebes Regency area. With the aim of helping the internet user community via the web. In this way, it is believed that it will be able to provide accurate information. This research displays digital maps on the web using the Google Maps API. With the belief that with an application that can clearly and completely display names, photos, descriptions and locations of hospitals, the number of health workers, the number of illnesses and the condition of babies born taken from the database contained in the Google DBMS, it can be easier to find out the number of health facilities. in Brebes district.